Methodology of the Comprehensive Program on Prevention and Control of Overweight and Obesity in Iranian Children and Adolescents: The IRAN-Ending Childhood Obesity (IRAN-ECHO) Program - Sayyari, Ali-Akbar (Int J Prev Med, 2017)
BACKGROUND: The World Health Organization program on Ending Childhood Obesity (WHO-ECHO) has developed a comprehensive and integrated package of recommendations to address childhood obesity. The present study, entitled IRAN-ECHO, was designed and implemented in the framework of the WHO-ECHO program. METHODS: The IRAN-ECHO program is implementing multicomponent interventions by considering life course dimensions. The program has two parts: a population approach and an individual approach. The population approach considers different periods in life, including prenatal, infancy, childhood, and adolescence, as well as family and society. The individual approach targets those children or adolescents with overweight or obesity; this part is conducted as a referral system that is now integrated in the current national health system. As part of the population approach, a quasi-experimental study was conducted in six provinces to compare the status before and after implementing parts of the interventions. By intersectoral collaboration with different organizations, multicomponent interventions are conducted for different age groups. RESULTS: The IRAN-ECHO program is being conducted in six provinces, and will be considered in all provinces in the near future. Its main effects could be assessed in future years. Part of this program that was conducted as a quasi-experimental survey comprised 7149 students and showed that a high percentage of students had acceptable knowledge about adverse health effects of overweight and obesity. However, the knowledge about the low nutritional value of unhealthy snacks such as potato chips, puffs, industrial juices, and carbonated drinks was not appropriate. Many participants had the undesirable attitude of skipping one of the main meals when attempting to lose weight. CONCLUSIONS: The IRAN-ECHO program is presenting the feasibility of conducting the WHO-ECHO recommendations in Iran. The scope of potential policy recommendations to decrease childhood obesity is extensive and includes various elements. This program considers multisectoral interventions through population and individual approaches. The multicomponent interventions of this program address the obesogenic environment by considering the life course dimensions. It is expected that, by its life course interventions, it could help in primordial and primary prevention of noncommunicable diseases.